Antimalarial Activity of Seed Extracts of Against in Mice - Abebe Basazn Mekuria; Mestayet Geta; Eshetie Melese Birru; Desalegn Asmelashe Gelayee (SAGE Publishing, 2021)
Background. Malaria is a major public health problem in developing countries. In Ethiopian, the seeds of Schinus molle are used for the management of malaria. Therefore, the current study aimed to evaluate in vivo antimalarial activity of hydro-alcoholic crude extract and solvent fractions of Schinus molle seeds in Plasmodium berghei infected mice. Methods. An 80 percent of methanolic crude extract and solvent fractions of Schinus molle seeds were tested for antimalarial activity at 100, 200 and 400 mg/kg doses. The parasitemia level, packed cell volume, body weight, survival of date and rectal temperature were used to evaluate the anti-malarial activity of the extracts. One-way ANOVA followed by post hoc Tukey's HSD multiple comparison test was employed and the result was expressed in mean ± SEM (standard error of the mean). Results. The curative activity of the highest dose of crude extract and aqueous fraction of Schinus molle seeds was 69.86% and 73.82% ( p < 0.001), respectively. In the prophylactic test, aqueous fraction had 72.39% ( p < 0.001) suppression antimalarial activity. Among solvent fractions, only chloroform fraction was significantly attenuated packed cell volume reduction. The mice treated with crude extract and aqueous fraction had longer survival date than vehicle-treated mice ( p < 0.001). Conclusion. The experiment finding showed that the crude extract and solvent fractions of Schinus molle seeds had significant curative and prophylaxis anti-plasmodial activity. This result revealed that the Schinus molle seeds extract has promising antimalarial activity against Plasmodium berghei . However, further confirmatory studies, isolation and characterization of the active constituents are recommended.